Perbandingan Kuantitas dan Kualitas Sperma Kambing Kacang, Kejobong, dan Peranakan Etawah - Rachmawati, Laili; Ismaya, Ismaya; Panjono, Panjono (2011)
This study was conducted to compare sperm quantity and quality of Kacang, Kejobong, and Etawah Cross Bred bucks. Nine heads twelve month old bucks which consist of three Kacang, three Kejobong and three Etawah Cross Bred bucks were used in this study. Sperm collected with Arti icial Vagina method, six times for each other with two days a week frequency. Macroskopic sperm examination included volume, smell, color, consistency and pH. Microskopic sperm examination included motility, viability, abnormality and concentration. The data were analyzed using, one way ANOVA and continued with Duncan's new multiple-range test. The results) showed that smell, color, consistency, pH, abnormality, and sperm concentration, had no significant value in each bucks. Volume and sperm motility Etawah Cross Bred bucks had significant value (P<0.05) to Kejobong and Kacang bucks, 1.06±0.50 ml; 0.57±0.16 ml and 0.56±0.21 ml; 65.56±9.17%; 46.67±14.79% and 42.22±16.41%, recpectively. Sperm viability percentage Etawah Cross Bred bucks had significant value (P<0.05) to Kacang bucks, 81.09±9.08 and 52.72±28.97. Sperm viability Kejobong bucks had no signi icant value to Kacang and Etawah Cross Bred bucks. It could be concluded that sperm quantity and quality Etawah Cross Bred bucks is better than sperm Kejobong and Kacang bucks. Key words: comparaticn, sperm quantity, sperm quality, kacang bucks, kejobong bucks, etawah cross bred bucks